Farm businesses, the digital economy, and broadband internet - Peter Stenberg; Mitchell Morehart (European Regional Science Association (ERSA), 2010)
Access to the Internet through broadband technologies has become a widely available, but not uniformly over space. Spatially-dispersed economic actors have lower Internet penetration rates, either out of choice or lack of local availability. We use data from the 2009 June Agricultural Survey, 2008 ARMS, and FCC broadband provider data to analyze farms, a specific sector of spatially-dispersed economic entrepreneurs. A majority of farms had Internet access, but only 1/3 of all farms used the Internet as an intergral part of their management operations. In addition, broadband Internet use was lower for farms than for urban economic actors. In this study we examine factors in Internet use and the technologies that farms use to get on-line. We show the difference in likelihood of broadband use with the likelihood of broadband provision and analyze the factors relative contribution through the use of logistic regression. The results suggest that both availability of the broadband Internet as well as the socio-economic characteristics of the farm operator influences the adoption of broadband Internet in their business.
Keywords: 330